2018
DOI: 10.1063/1.5024934
|View full text |Cite
|
Sign up to set email alerts
|

Single bead near-infrared random laser based on silica-gel infiltrated with Rhodamine 640

Abstract: Photoluminescence properties of single bead silica-gel (SG) embedded with a laser-dye were studied aiming at the operation of near-infrared (NIR) Random Lasers (RLs). The operation of RLs in the NIR spectral region is especially important for biological applications since the optical radiation has deep tissue penetration with negligible damage. Since laser-dyes operating in the NIR have poor stability and are poor emitters, ethanol solutions of Rhodamine 640 (Rh640) infiltrated in SG beads were used. The Rh640… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…6 (c) is the red-shift of the gain lineshape in the presence of the scatterer nanoparticles compared to the photoluminescence spectrum I0(λ). This phenomenon can be explained based on the reabsorption and reemission of light by the dye molecules [51]. The spectral overlap of RhB absorption and emission spectra emitted intensity (a.u.)…”
Section: Resultsmentioning
confidence: 99%
“…6 (c) is the red-shift of the gain lineshape in the presence of the scatterer nanoparticles compared to the photoluminescence spectrum I0(λ). This phenomenon can be explained based on the reabsorption and reemission of light by the dye molecules [51]. The spectral overlap of RhB absorption and emission spectra emitted intensity (a.u.)…”
Section: Resultsmentioning
confidence: 99%
“…By controlling the excitation fluence, it is possible to vary the random laser emission wavelength from 590 nm of 610 nm. Another tuneable random laser system was developed exploiting the presence of nanopores and the random structure of silica gel beads infiltrated with rhodamine 640 [27]. In this work, the authors demonstrated tunable RL emission in a range from 670 nm to 720 nm, which was attributed to reabsorption/reemission processes involving the dye molecules and their aggregates.…”
Section: Introductionmentioning
confidence: 98%
“…Of all materials, porous structures are particularly suitable platforms to design optically and electrically pumped RLs because light emission in these systems can be tailored by engineering the features of scattering centers (pores) through a variety of fabrication methods such as dry and wet chemical etching, template synthesis, and imprinting . Porous RLs can also be directly fabricated in materials with intrinsic light-emitting properties (e.g., semiconductors) or through functionalization of optically inert porous matrixes with light-emitting materials (e.g., fluorophores, semiconductor coatings, and quantum dots). , Recent advances in random-lasing technology have resulted in distinct forms of porous RLs such as etched semiconductors, organic fibers, nanowires, and porous ceramics . Nanoporous anodic alumina (NAA) produced by electrochemical oxidation (anodization) of aluminum substrates is a thin film of anodic aluminum oxide (alumina, Al 2 O 3 ) featuring hexagonally arranged, straight, cylindrical nanopores homogeneously distributed across its surface and along its thickness, from top to bottom. , This characteristic structure makes NAA an ideal platform material to develop lasing systems based on distinct forms of light–matter interactions.…”
Section: Introductionmentioning
confidence: 99%
“…21,26 Recent advances in random-lasing technology have resulted in distinct forms of porous RLs such as etched semiconductors, 27 organic fibers, 28 nanowires, 29 and porous ceramics. 30 Nanoporous anodic alumina (NAA) produced by electrochemical oxidation (anodization) of aluminum substrates is a thin film of anodic aluminum oxide (alumina, Al 2 O 3 ) featuring hexagonally arranged, straight, cylindrical nanopores homogeneously distributed across its surface and along its thickness, from top to bottom. 31,32 This characteristic structure makes NAA an ideal platform material to develop lasing systems based on distinct forms of light− matter interactions.…”
Section: ■ Introductionmentioning
confidence: 99%